1999
DOI: 10.1176/jnp.11.4.490
|View full text |Cite
|
Sign up to set email alerts
|

Remote Memory in Alzheimer's Disease

Abstract: The authors examined the severity and type of deficits in remote memory in patients with probable Alzheimer's disease (AD). In the first study, 40 AD patients showed significantly more severe deficits on both the free-recall and the recognition sections of the Remote Memory Scale (which measures memory for famous people and well-known events) compared with normal control subjects. In the second study, 25 AD patients showed significantly more deficits on the free-recall section of the Autobiographical Memory Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
2
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 16 publications
4
19
2
2
Order By: Relevance
“…In contrast, other studies found a TG in AD patients limited to recent periods using tests of famous people [13] or tasks combining famous people and public events [38], pointing to the anterograde amnesia as a plausible explanation for the results. Moreover, completely opposite patterns have also been found in AD when combining famous people and famous public events, whereby better performance was observed for recent rather than for remote periods [14]. Finally, no particular TG was found in a few other studies assessing memory for public events in AD and aMCI [15,18,23,39].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In contrast, other studies found a TG in AD patients limited to recent periods using tests of famous people [13] or tasks combining famous people and public events [38], pointing to the anterograde amnesia as a plausible explanation for the results. Moreover, completely opposite patterns have also been found in AD when combining famous people and famous public events, whereby better performance was observed for recent rather than for remote periods [14]. Finally, no particular TG was found in a few other studies assessing memory for public events in AD and aMCI [15,18,23,39].…”
Section: Introductionmentioning
confidence: 95%
“…Deficits in semantic memory have been extensively documented in AD using tests of famous people [9][10][11][12][13] and public events [13][14][15][16][17][18][19][20][21][22][23]. Studies have also demonstrated semantic impairment in aMCI using tests requiring the identification of famous people and famous buildings [11,12,[24][25][26][27][28][29], as well as public events [15,24,27,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, signs of semantic RA have been reported in samples of aMCI and AD patients using tests of famous public events [22][23][24][25][26][27] and tests of famous faces or famous names [28][29][30][31][32]. But also for this type of information mixed results regarding the temporal extent and gradient of RA have been reported [22][23][24][25]. From the above it is clear that, although interest in studying remote memory has grown exponentially over time, behavioral studies in aMCI and AD have produced ambiguous results and disagreement about the specific pattern of RA in these patients remains.…”
Section: Introductionmentioning
confidence: 62%
“…However, conflicting results have been reported about the presence or absence of a Ribot-like temporal gradient, with some authors reporting a significant temporal-graded amnesia in AD and aMCI [14,15,18] and others reporting no differences in memory recall between remote and recent incidents [19][20][21]. Similarly, signs of semantic RA have been reported in samples of aMCI and AD patients using tests of famous public events [22][23][24][25][26][27] and tests of famous faces or famous names [28][29][30][31][32]. But also for this type of information mixed results regarding the temporal extent and gradient of RA have been reported [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies agree that there is a deficit in this type of memory [37,[51][52][53][54][55][56][57][58], but there is disagreement about the pattern of the deficit: which component is more deteriorated, the episodic or the semantic? Which memories show a greater degree of decline, the recent ones or the remote ones?…”
Section: Autobiographical Memory Decline In the Course Of Alzheimer-tmentioning
confidence: 99%